Acute Toxicity Test of Jalembi Probiotic Beverages on Mice ddY - Anindita, Reza; Sari, Afrinia Eka (BERKALA SAINSTEK, 2023)
An acute toxicity test is one of the pre-clinical tests needed to determine the safety of the consumption of a product before clinical trials are carried out on humans. The purpose of this study was to confirm whether or not there was a toxic effect of jalembi juice probiotic drink (red guava, lemon, melon, beetroot) on male and female mice observed for 14 days. This research design is experimental. The samples in this study were jalembi probiotic juice drinks with Lactobacillus plantarum starter and 40 male and female ddY mice. This research procedure was carried out by giving jalembi juice as a test preparation with doses of 124, 640, 3200, and 16000 mg/kg BW as much as 0.59 ml in males and females mice. Data analysis was carried out with One-Way ANOVA. This study showed that the administration of probiotic drink jalembi juice with doses of 124, 640, 3200, and 16000 mg/KgBW as much as 0.59 ml did not cause death, changes in body weight, and clinical symptoms in all test animals. It can be concluded that the probiotic drink jalembi juice is categorized as practically non-toxic (> 15 g/KgBW) or passes pre-clinical testing as a safe drink for consumption.